Identification, distribution, and toxigenicity of obligate anaerobes in polluted waters. - Daily, O P (1981)
A seasonal occurrence of obligately anaerobic bacteria, predominantly of the genera Bacteroides and Clostridium, in a polluted water site has been observed. The number of anaerobes varied from 1.8 X 10(3) cells/ml in the warmer months to 10 cells/ml in winter. Several isolates were toxigenic, indicating a potential human health hazard.